NEW YEAR SPEECHES OF THE PRESIDENTS OF THE RUSSIAN FEDERATION ON TELEVISION IN 2000-2014: A COMPREHENSIVE STUDY / НОВОГОДНИЕ ВЫСТУПЛЕНИЯ ПРЕЗИДЕНТОВ РОССИЙСКОЙ ФЕДЕРАЦИИ ПО ТЕЛЕВИДЕНИЮ В 2000-2014 гг.: ОПЫТ КОМПЛЕКСНОГО ИССЛЕДОВАНИЯ - SHARIKOV A.V. / ШАРИКОВ А.В.; MITSUK T.I. / МИЦУК Т.И. (Наука телевидения)
Presidential New Year’s greetings are interesting in a way that all the major TV channels simultaneously broadcast the same thing. How is the audience distributed between the channels during these minutes of the annual maximum of the TV viewing? The audience of V.V. Putin—«First channel» D.A. Medvedev—«Russia 1», NTV. In New Year congratulations of V.V. Putin, most used categories are «year», «dear», «friends», «Russia», «own», D. A. Medvedev—«close», «be», «all», «you», «do», «wish», «love»...